THE IMPACT OF WORK-LIFE QUALITY ON HOTEL EMPLOYEE PERFORMANCE - Rachel Dyah Wiastuti; Stephan Collindes Adi; Sarim Sarim; Basri Rashid (Jurnal Manajemen Perhotelan, 2023)
The purpose of this research is to identify the impact of work-life quality on hotel employee performance. This study used a quantitative approach. Primary data was collected through a survey using face- to- face questionnaire to 134 hotel employees. Data were analyzed with descriptive statistics, correlation, and regression using SPSS. The result indicated that work-life quality has a significant influence on employee performance with a value of 34.1 percent, in which both showed a moderate correlation but were significant and positive. This implies that the higher the work-life quality, the higher the employee performance will be, and vice versa. This study implication presents recommendations for the hotel industry specifically on how to keep the company competitive advantage through work-life quality and employee performance. To add, this study also contributes to the human resources literature in the hospitality context.